A validated methodology for patient specific computational modeling of self-expandable transcatheter aortic valve implantation. Issue 13 (6th September 2016) - Bosmans, Bart; Famaey, Nele; Verhoelst, Eva; Bosmans, Johan; Vander Sloten, Jos
Abstract: Leakage of blood alongside the implant is a relatively frequent and life-limiting complication after transcatheter aortic valve implantation. The aim of this study is to develop and validate a workflow to simulate the implantation prior to the intervention. Based on the simulation outcome, the amount of leakage is estimated in order to evaluate the risk of a severe complication. A finite element model of the stent implantation in 10 patients was created based on a pre-operative computed tomography scan. All 10 patients also received a follow-up computed tomography scan, after the implantation. This scan was used to extract the deformed geometry of the stent and the position of the calcifications for validation of the simulation results. The maximal average perimeter difference between the simulated stent and the post-operative stent is 2.9±2.1 mm, and occurs at the bottom of the device. The sensitivity of the simulation to the soft tissue material parameters and aortic root wall thickness was tested. The maximal diameter deviation of 6% occurred when the thickness of the aortic root was doubled. The result of the leakage analysis based on the distance between the simulated stent and the surrounding aortic root corresponded well when no regurgitation was observed. The developed tools have the potential to reduce the occurrence and severity of leakage by providing the clinician with additional information prior to the intervention. The simulated geometry and estimated leakage can help decide on the best implant type, size and position before treatment.